KAMPUNG JAWA TONDANO DALAM PERSPEKTIF ARKEOLOGI RUANG - Anindya Puspita Putri; Henki Riko Pratama (Aqlam: Journal of Islam and Plurality, 2024)
Abstract : The interaction between humans and the environment creates a cultural landscape which is a concrete manifestation of human adaptation to the environment. This research discusses Kampung Jawa Tondano in the scope of spatial archeology. Kampung Jawa Tondano is a famous historical settlement in Minahasa Regency, North Sulawesi. This village was founded by Kiai Mojo and his followers when they were exiled in Tondano. This research aims to look at the spatial dynamics and cultural continuity of Kampung Jawa Tondano from a spatial archaeological perspective. Most villages in Indonesia are created from cultural patterns. The character of a village based on Muslim residents and becoming a center for spreading religion is called an Islamic Village or Kauman. Kauman is not applied in the Kampung Jawa Tondano, the term kauman does not appear in the spatial expression in this village. The condition of exile status of minority community groups in Kampung Jawa Tondano is certainly a reason for not emphasizing religious aspects compared to tribal identity. Other components of the settlement in Kampung Jawa Tondano that have a relationship with Islamic and Javanese culture are the Al-Falah Mosque building and the Kiai Mojo Complex Tomb. The mosque building adopts the concept of a traditional Javanese mosque building. The placement of the Kiai Mojo Complex Tomb on a hill is evidence of the continuity of Javanese culture.Key Words : Settlement, Spatial Archaeology, Kampung Jawa Tondano, CultureAbstrak : Interaksi antara manusia dengan lingkungan menciptakan bentang budaya (cultural landscape) yang merupakan kenampakan konkrit dari hasil adaptasi manusia terhadap lingkungan. Kajian ini membahas tentang Kampung Jawa Tondano dalam lingkup arkeologi ruang. Kampung Jawa Tondano merupakan permukiman bersejarah yang terkenal di Kabupaten Minahasa, Sulawesi Utara. Kampung ini didirikan oleh Kiai Mojo dan pengikutnya ketika diasingkan di Tondano. Penelitian ini bertujuan melihat dinamika keruangan dan kesinambungan budaya Kampung Jawa Tondano dalam perspektif arkeologi ruang. Kebanyakan kampung di Indonesia tercipta dari corak budaya. Karakter kampung yang didasari oleh penduduk beragama Islam dan menjadi pusat penyebaran agama disebut sebagai Kampung Islam atau Kampung Kauman. Penyebutan nama Kampung Kauman tidak diterapkan di Kampung Jawa Tondano, sebutan kauman tidak tampak dalam ekspresi ruang di kampung ini. Kondisi status pengasingan dari kelompok masyarakat minoritas di Kampung Jawa Tondano tentunya menjadi alasan untuk tidak menonjolkan aspek religi dibandingkan identitas kesukuan. Komponen permukiman lainnya di Kampung Jawa Tondano yang memiliki relasi dengan budaya Islam dan Jawa adalah bangunan Masjid Al-Falah dan Kompleks Makam Kiai Mojo dan pengikutnya. Bangunan masjid mengadopsi konsep bangunan masjid tradisional Jawa. Penempatan Kompleks Makam Kiai Mojo dan pengikutnya di atas bukit merupakan bukti adanya kesinambungan budaya Jawa. Kata Kunci : Permukiman, Arkeologi Ruang, Kampung Jawa Tondano, Budaya